MODERN APPROACHES TO NUTRITIONAL SUPPORT OF PATIENTS AFTER SOLID ORGAN TRANSPLANTATION - M. Sh. Khubutiya; A. A. Ryk; E. A. Tarabrin; A. V. Grishin; T. E. Kallagov; A. V. Vodyasov; I. I. Utkina (Трансплантология (Москва))
.